The Strategies for Administration and Management of Small-Size Education Institutions in Future Scenario ( B.E. 2556 -2565) In the Upper Northern part of Thailand Under the Office of Basic Education Commission - Sunkawn, Chai; Yavirat, Poonchai (Ratchaphruek Journal, 2014)
The purposes of this study was to study the strategies for administration and management of small-size schools attached to Office of the Basic Education Commission. The population used in the study were small-size school in the northern of Thailand which were from the inspectional zone 15-16 of Educational Ministry. The informants were 1) leaders and administrators, 2) the strategic executive leaders who have well extensive experiences in researching of strategies and education management, 3) an administrators in the small-size school and the educators or the social leaders who work with strategies. The research operation is divided into four phases ; data collected by questionnaire, interview, ethnographic futures research techniques, SWOT Matrix and the evaluate form. The research findings revealed that: 1. All small-size schools comprised 6 components of school administration and management. The result divided 6 components into 2 groups. The first group was those who held back the management of small-size schools lacking in quality ;the finance and assets management , general Management and personnel management. The second group was those who promoted the management of small- sizes schools ; the academic management, the structure component, and management of technology. 2. The future scenarios of the management of small-size schools must be accelerated in developing of educational quality and standard using area or community-based management to develop the students skills and appropriate attributes toward the 21st century. The small-size schools should develop the strong point or show the best practices for all sectors to participate in educational management. They should have a long-life learning and should learn via advanced and rapid technology network. The schools should manage the community-based in learning process. 3. The strategies management of small-size schools attached to the Office of the Basic Education Commission in BE 2556-2565were developed a strong network of small-size schools, used ICT in teaching and in educational administration and management, strengthen the system of school management systematically, establish the of the uniqueness institution and develop the identity of learners .